PENGARUH KUALITAS PELAYANAN SUMBER DAYA MANUSIA TERHADAP KEPUASAN MASYARAKAT DI PUSKESMAS KELURAHAN JAGAKARSA I TAHUN 2012 - Marulloh Marulloh (KENEGARAAN, 2016)
Minimum Service Standards (MSS) is a minimum standard of public service that must be provided by the government to the community, is a measure of the performance of the organizers of the responsibilities associated with the basic services to the community, one of the services referred to in the form of health care. it raised problem that is not optimal satisfaction of community service at Puskesmas Kelurahan Jagakarsa I While the purpose of the research is to determine the effect of the service quality of human resources at Community Puskesmas Kelurahan Jagakarsa I to the satisfaction of the public in 2012. This study uses quantitative analysis with a descriptive approach. The results obtained are all items tested valid and reliable questionnaire and outcomes measurement correlation coefficient 0.977; coefficient of determination 0.954, and a regression coefficient 0.774. Based on these results, it is concluded that there is an influence of the service quality human resources to the satisfaction of the public. In addition to, the quality of human resources that affect the satisfaction of the public service, there are other things that also affect the satisfaction of the public service, which is available of equipment, coordination and leadership. Therefore, factors other than improving the quality of human resources should also get attention, so that people's needs can be fulfilled properly.Keywords: service quality and public satisfaction